2018
DOI: 10.1177/1479164118769528
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the combination of isosorbide dinitrate spray and chitosan gel for the treatment of diabetic foot ulcers: A double-blind, randomized, clinical trial

Abstract: Aim: To evaluate whether a combination of isosorbide dinitrate spray and chitosan gel (10%) topically applied can have additive benefits for management of diabetic foot ulcers. Methods: In a randomized, placebo-controlled, double-blinded clinical trial, 68 patients were divided into four groups: Group 1: treated with chitosan gel; Group 2: isosorbide dinitrate spray; Group 3: combination of isosorbide dinitrate spray and chitosan gel; Group 4: placebo. Results: Histological analyses showed a significant regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
(10 reference statements)
0
15
0
1
Order By: Relevance
“…Two recent RCTs with topical Pirferidone (with potential anti‐inflammatory/antifibrotic properties) had methodological limitations; neither were blinded, results were analysed per protocol, and there was a high dropout rate in one, and an unexpectedly low healing rate in the control group in the other . Four RCTs of products designed to promote healing; Chitosan and Isosorbide dinitrate, hyaluronic acid, an acellular flowable matrix, and the proteolytic fraction from latex P1G10 provided little support for the use of these agents in clinical practice because of a small number of recruited patients, nonblinding, per protocol analysis, and/or high drop‐out rates. One RCT of a gap‐junctional protein (ACT1, a connexin43‐based gel) in patients with noninfected neuropathic ulcers showed a significantly greater reduction in mean percent ulcer area from baseline to 12 weeks but with a high rate of withdrawal of consent and protocol noncompliance …”
Section: Recommendationsmentioning
confidence: 99%
“…Two recent RCTs with topical Pirferidone (with potential anti‐inflammatory/antifibrotic properties) had methodological limitations; neither were blinded, results were analysed per protocol, and there was a high dropout rate in one, and an unexpectedly low healing rate in the control group in the other . Four RCTs of products designed to promote healing; Chitosan and Isosorbide dinitrate, hyaluronic acid, an acellular flowable matrix, and the proteolytic fraction from latex P1G10 provided little support for the use of these agents in clinical practice because of a small number of recruited patients, nonblinding, per protocol analysis, and/or high drop‐out rates. One RCT of a gap‐junctional protein (ACT1, a connexin43‐based gel) in patients with noninfected neuropathic ulcers showed a significantly greater reduction in mean percent ulcer area from baseline to 12 weeks but with a high rate of withdrawal of consent and protocol noncompliance …”
Section: Recommendationsmentioning
confidence: 99%
“… 13 In a previous clinical study, CS was found to be a promising dressing material for faster wound healing in patients with chronic wounds, such as diabetic foot, pressure ulcers, and vascular ulcers. 14 15 Acylated CS fibers demonstrate a high absorbency ability of wound exudate, a faster healing time, and an increased pain relief effect in chronic wounds. 14 Our material was based on a woven CS fiber membrane that was additionally compounded with alginate to augment the absorbency of the wound exudate.…”
Section: Discussionmentioning
confidence: 99%
“…For completeness, studies that were previously reported in the 2016 systematic review that are not discussed in the present document have been included in the supplementary tables …”
Section: Acknowledgementsmentioning
confidence: 99%